Application of Particle Swarm Optimization in Overturning Moment of Crawler Crane. Issue 1 (February 2021) - Xu, Haixiang; Zhang, Ye; Lei, Juyang; Wu, Fengqi; Gong, Wen
Abstract: The rotating angle is one of the important operation parameters of jib crane, while the on-site survey of slewing angle is a difficult problem to evaluate the accuracy of angle display. This paper put forward a survey methodology based on the coordinate data around the rotation of marked points on the crane boom, and constructed the cost function by the geometric relations of marked point trajectory, used the particle swarm optimization algorithm to find the optimal solution of estimated angle. The simulation, laboratory experiment and on-site tests showed the survey methodology has the satisfied accuracy and be easy to implement.